Winter flood significantly changes salinity and nutrient export from land to sea - Bussmann, Ingeborg; Brix, Holger; Flöser, Götz; Fischer, Philipp F.; Jayachandran, Saranya; Achterberg, Eric P.; Carstens, Kristine; Kirstein, Inga V.; Sanders, Tina; Raupers, Björn; Voynova, Yoana; Kamjunke, Norbert (Frontiers in Marine Science, 2025)
Flood events caused by high rainfall can have profound biogeochemical impacts on riverine systems but also on the receiving coastal waters. The winter flood in Germany in December 2023/January 2024 affected the Elbe and Weser River systems. We obtained unique data during the peak of the flood and compared these with the monthly means from previous years (2018-2023). Hydrographic parameters and nutrients were determined by standard methods. Low salinity values were observed in the Elbe estuary and the adjacent German Bight (part of North Sea). At Helgoland the lowest average salinity was observed in January 2024 with 31.3 ± 0.5 compared to an average salinity of 32.7 ± 0.7 for the years 2016 to 2023. Nutrient loads (nitrate, phosphate) in the rivers showed a six- to 11-fold increase in the Elbe and Weser rivers compared to years without flood events. Enhanced concentrations of nitrate and silicate were found in the German Bight in January. Nutrients were diluted with North Sea waters, indicating a conservative behavior of nutrients in winter. Atypical prevailing meteorological conditions in January 2024, with predominantly easterly winds, potentially affect the dispersal of the river plume and the nutrients in the North Sea. In March 2024 the chlorophyll-a concentration strongly increased to 2.9 ± 1.8 µmol/L and was twice as high compared to only 1.5 ± 0.7 µmol/L observed in previous years. The observed intensified spring bloom in March in the German Bight near the island of Helgoland indicates the impacts of the flood-derived nutrient inputs three months after the flood event, as the timing of light and nutrient availability was optimal. It is assumed that seasonality and magnitude of flooding in the Elbe estuary and adjacent coastal region will change in future due to climate warming. Thus, the timing of light and nutrient availability will also change, with unconstrained impacts on primary producers and higher trophic levels.